Perancangan Pengalaman Pengguna Sistem Pembelajaran Etika Komunikasi Mahasiswa Universitas Brawijaya Dengan Konsep Gamifikasi Menggunakan Pendekatan Player Centered Design - Mohammad Khaufillah; Hanifah Muslimah Az-Zahra; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Brawijaya University has thousands of students with diverse backgrounds. Almost all student in Brawijaya University using smartphone for daily activities. The intensity of smartphone usage can affect communication behavior. It can be formed differences in the procedures or ethics of directly communicating and through information technology media, especially communication between students and lecturers. Therefore, we need a system with quality educational content to help Brawijaya University students to make positive communication behavior within the University of Brawijaya environment. To attract students' interest, an interactive and fun system is needed. This requires the concept of gamification in designing systems. The concept of gamification was chosen because the concept supports motivation improvement through the psychological side of the game element, namely through a combination of challenges, feedback, and rules. So that it can reduce the cost burden of implementing the system. To support the concept of gamification, a Player Centered Design approach is needed as a flow in system design. The design process produces 13 system requirements, 5 mission definitions, 6 motivation definitions, and the final result is a high fidelity prototype. In this research using testing process to generate some design improvement from user. Testing process in this research is using playtesting method. It has 2 iterations. In first iteration produce 8 system improvement designs and second iteration produce 1 system improvement design.